PERJANJIAN LISENSI MEREK TERKENAL - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
Licensing agreement is an approach to protect the exclusive right of trademark. This agreement contains the principles of freedom of contract, mutualism, the utmost good faith, onsensualism, and equality. Any dispute regarding the licensing agreement of a well-known mark may be resolved in a court trial or in an arbitration.